Analysis of human and artificial intelligence influencing cyber threats in Malaysian financial sectors. - Lau, Pei Ying; Rosita Anne, Rajanthiram; Sabrina, Abdul Karim; Teoh, Yuan Chi (2023)
The use of technology has brought about a variety of changes to the financial sectors. The development of more advanced technologies has, on the one hand, made it easier for the financial sectors to carry out their regular business; on the other end of the spectrum, this has also led to an increase in the number of cyber threats. With the advent of artificial intelligence, new models for finding and avoiding cyber threat have emerged. To avoid falling prey to deception, everyone needs to educate themselves on the capabilities of artificial intelligence. Therefore, both the human and artificial intelligence perspectives have been taken into account in this research. The purpose of this study is to expand on the fraud diamond theory by providing a more comprehensive analysis of the motivations that drive dishonest individuals to engage in fraudulent behavior. On the other hand, this study also seeks to expand on the self-determination theory by bolstering pre-existing view of how characteristics that help people learn artificial technology and help the latter avoid becoming victims. In this research, we examine how human and artificial intelligence factors are related to the like hood of cyber threats, and we speculate that fraudulent cases may play a mediator role. A questionnaire was used to obtain the data from a total of 384 adults in Malaysia. Partial Least Square-Structural Equation Modelling (PLS-SEM) software was used to analyze the collected data. We find that fraudulent cases are associated with pressure and opportunity. The findings of our paper implies that fraudulent cases influence the relationship between the two fraud risks and cyber threats.